2022
DOI: 10.3389/fgene.2022.866819
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of 7-methylguanosine and immune microenvironment characteristics in clear cell renal cell carcinomas

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most common tumors in the urinary system. ccRCC has obvious immunological characteristics, and the infiltration of immune cells is related to the prognosis of ccRCC. The effect of immune checkpoint therapy is related to the dynamic changes of the tumor immune microenvironment (TIM). The 7-methylguanosine (m7G) is an additional mRNA modification ability besides m6A, which is closely related to the TIM and affects the occurrence and development of tumors. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The risk score was computed via genes linked to prognosis, i.e., SRGs and FRGs. However, no prior studies The expression level of PD-L1 and CTLA-4 was remarkably elevated in the low-risk category relative to the highrisk category, congruent with literature findings [44,45]. ICIs are common immunomodulatory monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 77%
“…The risk score was computed via genes linked to prognosis, i.e., SRGs and FRGs. However, no prior studies The expression level of PD-L1 and CTLA-4 was remarkably elevated in the low-risk category relative to the highrisk category, congruent with literature findings [44,45]. ICIs are common immunomodulatory monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 77%
“…According to previous research, high urinary hypoxanthine levels can be related to respiratory disorders and deficiencies in hypoxanthine-guanine phosphoribosyltransferase to acute renal failure in infants [52,53]. Additionally, 7−methylguanosine, the modified purine nucleoside, showed significant VIP scores, associated with ischemic diseases and identified as a biomarker in cancer studies [54,55]. In brief, these upregulations suggest significant metabolic mechanisms related to kidney and respiratory development.…”
Section: Identification Of Differential Metabolites In Preterm Infant...mentioning
confidence: 90%
“…A large number of studies indicate that METTL1 is upregulated in solid tumors, which often predict poor survival (13). Some studies also have shown that m7G-related genes(EIF3D, EIF4E1B, LARP1, NCBP1, GEMIN5, and DCP2) are associated with the progression of tumors as well as the prognosis of patients (14,15,16). In Bca, whether m7G can regulate the occurrence and development of tumors, and how M7G key genes and related gene expressions are still unknown Tumor microenvironment (TME) is a complex system with various stromal cells, such as broblasts, vascular endothelial cells, immune cells, adipocytes, mesenchymal stem cells, and various cytokines (17).…”
Section: Introductionmentioning
confidence: 99%